2018
DOI: 10.22374/1875-6859.14.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Differences of Household Income and Physical Fitness Variables in Elderly Koreans

Abstract: Background and Objective Physical activity and fitness are complementary to each other, but they are independent concepts with regard to health. Although there are some studies about the relationship between one’s physical activity and economic level, there are very few studies about the relationship between one’s fitness level and economic level. Therefore, this study aimed to investigate the fitness level of elderly Koreans according to their economic level.   Material and Methods In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This difference did not appear to be significant. Research by Ahn and So (2018), stated that the lower body flexibility was 5.36±9.02 for older Korean men and 11.64±8.76 cm for women, with upper body flexibility of -12.83±13.71 cm for men and -5.51±12.69 cm for women. According to these results, the lower body flexibility of our older women and older men was less compared to Korean women and men, while for upper body flexibility, our older women were worse while our older men were better (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference did not appear to be significant. Research by Ahn and So (2018), stated that the lower body flexibility was 5.36±9.02 for older Korean men and 11.64±8.76 cm for women, with upper body flexibility of -12.83±13.71 cm for men and -5.51±12.69 cm for women. According to these results, the lower body flexibility of our older women and older men was less compared to Korean women and men, while for upper body flexibility, our older women were worse while our older men were better (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Physical fitness components and physical activity level with no statistical significance between genders between this research performed on the elderly Turkish group and our research results (Toraman & Ayçeman, 2005). In research investigating the correlation between the income levels and physical fitness of elderly Korean individuals with a mean age of 71.81 years, Ahn and So (2018) stated the sitstand result for men was 16.94, while it was 15.54 for women. In our research, though the mean age of men and women was 70 years, these values appear to be slightly low (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that unfamiliar places may lead to older adults experiencing falls and developing FOF [16]. Third, housing is an indirect indicator of poverty; renters are a proxy for low socioeconomic status (SES) or low income, and low incomes are highly associated with low physical activity [25,26]. A previous study indicated that renters showed increased odds of drug and healthcare nonadherence, poor self-reported health, vascular disease, and arthritis [27].…”
Section: Discussionmentioning
confidence: 99%